The Correlation between Polymorphism of β Fibrinogen Gene -455 G/A and Serum Fibrinogen Level with The Severity of Coronary Artery Stenosis In Coronary Artery Disease Patient - Indrajaya, Taufik; Fadilah, Yudhi; Yuwono, Mediarty; Ghanie, Ali (Bangladesh Journal of Medical Science, 2019)
Background: Now a days coronary artery disease (CAD) becomes major cause of death. One among 7 deaths in America caused by CAD. CAD is an atherosclerosis process, which progresively develops into plaque that will lead to stenosis of coronary artery lumen. Several studies found that high serum fibrinogen level is an independent and significant to the severity of artery coronary stenosis. Serum fibrinogen level determined by genetic factor. Polymorphism of fibrinogen gene β -455 G/A seem plays an important role in plasma fibrinogen level. Although some studies showed a significant correlation between polymorphism and cardiovascular diseases, but some other studies report inversely. Aim. To evaluate the correlation between the polymorphism of fibrinogen gene β -455 G/A and serum fibrinogen level with the severity of artery coronary stenosis. Method: This is an analytic correlative study with prospective approach without comparison. Coronary angiography was performed in catheterization labor in the department of internal medicine, while DNA analysis and PCR done in the department of microbiology in General Hospital dr Muhammad Husin Palembang- Indonesioa, since July 2015 until Agustus 2016. Samples are CAD patient who undergo for coronary angiography and fulfield the criterias. The severity of stenosis in coronary artery determined by Gensini score. This study included 31 patient. Results. Among 31 CAD patients, this study found severe stenosis of coronary artery in 17 patients (53,1%), moderate in 5 patients (15,6%) and mild in 10 patients (31,2%). Genetic analysis showed that serum fibrinogen level was controlled by polymorphism of fibrinogen gene β -455 G/A, concecutively by genotipe AA in 15 patients (48,4%), genotipe GA in 12 patient (38,7%) and by genotipe GG in 4 patients (12,9%). Chi Square test showed a significant correlation between polymorphism gene fibrinogen β -455 G/A and serum fibrinogen level (p=0,039). Spearman’s rho test found no significant correlation between serum fibrinogen level and severity of coronary artery stenosis based on Gensini score (r=0,142; p=0,447). And also this study found no significant correlation between polymorphism gene fibrinogen β -455 G/A with the severity of stenosis in coronary artery (p=0,512). Conclusion. Although this study succeded to prove that serum fibrinogen level was determined by polymorphism fibrinogen gene β -455 G/A, but there are no significant correlations between polymorphism fibrinogen gene β -455 G/A and serum fibrinogen level with severity of coronary artery stenosis in CAD patients. This study suggest to study other candidate gene to look for other cardiac risk beside this fibrinogen. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.379-384